Muhammadiyah and the Shifting Interpretation of Local Religious Traditions - Akhmad Arif Junaidi (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2022)
The study focuses on changes in the religious interpretation of the Muhammadiyah, an Islamic mass organization in Indonesia, which initially sought to clear Islam from local religious traditions but then began to accept the tradition. This research is qualitative research, with documented methods and in-depth interviews, to explore to what extent these changes and the factors affecting them. The study reveals that Muhammadiyah began tolerating local religious traditions and emphasized the need to redefine religious purification. Factors such as less popular da’wah strategies in rural areas, and the emergence of young Muhammadiyah groups supporting liberalism and moderation, have influenced this shift. This study is important to advance scientific traditions, especially in relation to Muhammadiyah, and to make constructive contributions to formulating organizational policies in connection with local religious traditions.